2020
DOI: 10.1155/2020/2194873
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial: Comparison of 4% Articaine versus 0.5% Bupivacaine for Ambulatory Orthopedic Surgery under Supraclavicular Block

Abstract: Background. Articaine has been used in many dental and ophthalmic outpatient procedures. In the era of ultrasound-guided regional techniques, we searched for short and potent local anesthetic for patients undergoing ambulatory upper limb procedures. However, studies about articaine efficacy in brachial plexus block are limited. In this study, we compared its safety and efficacy against bupivacaine as a commonly used anesthetic agent for ultrasound-guided supraclavicular brachial plexus block. Methods. This ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…Our study agrees with a study done by Eldemrdash and Abdelzaam [9] , in which they showed the effects of articaine 2% with adrenaline during erector spinae plane block for assessment of postoperative analgesia after radical mastectomy. Also, our study agrees with a study done by Armanious and Abdelhameed [32] , in which they showed the effects of articaine 2% versus bupivacaine for ultrasound-guided supraclavicular brachial plexus block. That study concluded that articaine is an efficacious and reliable alternative to bupivacaine.…”
Section: Discussionsupporting
confidence: 93%
“…Our study agrees with a study done by Eldemrdash and Abdelzaam [9] , in which they showed the effects of articaine 2% with adrenaline during erector spinae plane block for assessment of postoperative analgesia after radical mastectomy. Also, our study agrees with a study done by Armanious and Abdelhameed [32] , in which they showed the effects of articaine 2% versus bupivacaine for ultrasound-guided supraclavicular brachial plexus block. That study concluded that articaine is an efficacious and reliable alternative to bupivacaine.…”
Section: Discussionsupporting
confidence: 93%